2023
DOI: 10.7554/elife.82311
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent fasting induces rapid hepatocyte proliferation to restore the hepatostat in the mouse liver

Abstract: Nutrient availability fluctuates in most natural populations, forcing organisms to undergo periods of fasting and re-feeding. It is unknown how dietary changes influence liver homeostasis. Here, we show that a switch from ad libitum feeding to intermittent fasting (IF) promotes rapid hepatocyte proliferation. Mechanistically, IF-induced hepatocyte proliferation is driven by the combined action of systemic FGF15 and localized WNT signaling. Hepatocyte proliferation during periods of fasting and re-feeding re-es… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 42 publications
3
8
0
Order By: Relevance
“…Moreover, the pericentral hepatocytes temporally acquire a more periportal hepatocyte phenotype, at least at the level of gene expression. Sarkar et al have reported that intermittent fasting interacts with WNT signaling, which is consistent with our findings 56 . Previous studies have demonstrated that the WNT signaling gradient is established at the time of weaning and is a necessary regulator of hepatocyte lobule zonation 57,58, 59 .…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, the pericentral hepatocytes temporally acquire a more periportal hepatocyte phenotype, at least at the level of gene expression. Sarkar et al have reported that intermittent fasting interacts with WNT signaling, which is consistent with our findings 56 . Previous studies have demonstrated that the WNT signaling gradient is established at the time of weaning and is a necessary regulator of hepatocyte lobule zonation 57,58, 59 .…”
Section: Discussionsupporting
confidence: 94%
“…We also observed robust structural changes in the livers of IF mice (Fig 1K and Appendix Fig S1B), where hepatocytes showed an oedematous morphology. This hepatocyte oedema resembled the one reported upon 1‐week of IF as a compensatory mechanism to fluctuating liver size between the fasting and fed states (preprint: Sarkar et al , 2021). Our data show that liver remodelling persists after 3 months of IF.…”
Section: Resultssupporting
confidence: 77%
“…A previous study in Rosa26-Cas9 knock-in mouse showed that constitutive SpCas9 expression did not result in any detectable toxicity or morphological abnormalities in multiple organs (including the brain, kidney, liver, spleen, and heart tissue) of this transgenic strain [ 24 ]. Multiple studies have provided evidence of the safety of Cas9 mice by showcasing the utilization of diverse tissues and cells from these murine models [ 34 , 35 , 36 ]. However, long-term SpCas9 expression and its associated toxicity have not been characterized in ocular tissues in these mice, which can be bred for germline transmission of the Cas9 allele.…”
Section: Discussionmentioning
confidence: 99%